Pengaruh Model Pembelajaran Talking Stick Terhadap Motivasi Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas VIII SMP Negeri 4 Tarutung Tahun Pembelajaran 2023/2024 - Tiarma Fitri Br. Malau; Sandy Ariawan; Lince R.T Simamora; Hisardo Sitorus; Sabar Rudi Sitompul (Populer: Jurnal Penelitian Mahasiswa, 2024)
The aim of this research is to find out whether there is a significant influence of the Talking Stick learning model and the learning motivation of class VIII students at SMP N 4 Tarutung for the 2023/2024 academic year. The method used in this research is a quantitative method with a pre-experimental designs research type in the form of a one-group pretest-posttest design. The population was all Protestant Christian students in class VIII of SMP Negeri 4 Tarutung consisting of 4 classes totaling 121 students and a sample of 31 people was determined using purposive sampling. Data was collected using a closed questionnaire with 30 items. The results of data analysis show that there is a positive and significant influence on the Talking Stick learning model on the learning motivation of Christian Religious Education students and character in class VIII SMP Negeri 4 Tarutung for the 2023/2024 academic year as evidenced by the significant test obtained by the value tcount > ttable (α=0 .05; dk=n-1=30) which is 7.197 > 2.042, thus there is a significant influence between variable X and variable Y. Thus H0 is rejected and Ha is that there is a positive and significant influence on the Talking Stick learning model on learning motivation students of Christian Religious Education and character education in class VIII of SMP Negeri 4 Tarutung for the 2023/2024 academic year were accepted.